INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PERUSAHAAN PUBLIK DI INDONESIA - Indra Suyoto Kurniawan (University of Merdeka Malang, 2013)
The purpose of this study was to examine the relationship between the efficiency of the value added to thecompanys resources in the main components (physical capital, human capital, structural capital) and researchersare trying to add the market value of the three dimensions of a companys financial performance isROA, ATO, and GR. The data is taken from the 44 public companies engaged in non financial sector for 3 years(2009-2011). This study is an empirical study using PLS as a data analysis tool. The findings of this studysuggest that having an IC on the financial performance of the company, the IC also has a positive effect on thefinancial performance of companies in the future. While the rate of growth for the company IC (ROGIC) within3 years of observation there is a difference, where to ROGIC2009-2010 does not affect the financial performance in2010, ROGIC2010-2011 positive effect on the financial performance for the year 2011. The findings suggest thathuman capital (VAHU) and physical capital (VACA) is an indicator of a positive effect IC for two years ofobservation, while the capital structure (STVA) has a positive effect only in 2010 while the market value (MV)effect only in 2011. While the ROA and the ATO as an indicator of financial performance consistent effect forthree years of observation. And for the year 2010 was significant for all indicators either IC or financialperformance.